ISOLASI MIKROBA ASLI TANAH ANDISOL DIENG DAN KAJIAN POTENSINYA SEBAGAI INOKULAN PUPUK HAYATI PELARUT FOSFAT - Sudadi Sudadi; Hery Widijanto; Linda Habsari Efendi Putri (Faculty of Agriculture, Universitas Sebelas Maret, 2013)
Title : Isolation of Indigenous Phosphate Solubilizing Microbia from Andisols Dieng and Its Potency as Inoculum of Phosphate Solubilizing Biofertilizer. Phosphor (P) is an essential macro nutrient that occur frequently in low availability for plant. This research aimed to find indigenous phosphate solubilizing microbia from Andisols Dieng as biofertilizer inoculum. It was conducted in UNS Soil Biology Laboratory, Faculty of Agriculture, UNS. The research was begun with an exploratory research to obtain P solubilizer isolates (PSB). Research continued by two experiment, set by a completely randomized design (CRD) with two factors: kind of isolate from Andisols Dieng and incubation time. The first experiment was conducted in temporary period in the pikovskaya liquid medium. The second experiment was conducted in vermicompost its carrier. Each treatment combination was repeated 3 times. As much as 106cell or spore was inoculated per gram of medium or vermicompost. Dissolved P , biomass or cell density, and pH at 0,1, 3 and 6 days after incubation for the pikovskaya liquid medium and at 0, 2, 4 weeks for vermicompost. The results showed that there were 4 isolates potential to be inoculums of P solubilizer biofertilizer, they were are isolates of bacteria (P1), Aspergillusniger, Fusarium sp, and Aspergillus tamarii. Aspergillus niger is the most potential inoculums as it highest viability and dissolving phosphate both in liquid media (2.83me/l), and vermicompost (36.78% ).